Mitochondrial DNA mutations in cancer - Greaves, Laura (Henry Stewart Talks, 2024)
Mitochondrial function and mitochondrial genetics, Mitochondrial DNA mutations in cancer, Mitochondria and oxidative phosphorylation, Mitochondrial DNA mutations in early stage intestinal tumorigenesis, Mitochondrial DNA mutations in malignant melanoma